PENGARUH EKSTRAK DAUN SIRSAK (Annona muricata)TERHADAP KADAR KOLESTEROL TOTAL PADA MODEL TIKUS PUTIH GALUR WISTAR (Rattus norvegicus)HIPERKOLESTEROLEMIA-DIABETES - Muhammad Fawwaz Farhan (2020)
Diabetes mellitus is a disease with the highest number of sufferers in the world. In 2015, there were estimates of approximately 415 million people or around 8.8 percent of the entire world population calculated from the age of 20 - 79 years and predicted to increase to 642 million people or 10.4 percent of the entire world population in 2040. Soursop leaf extract (Annona muricata) has antioxidants in the form of flavonoids which can reduce total blood cholesterol levels. This study aims to determine the effect of soursop leaf extract on total blood cholesterol levels in a hypercholesterolemia-diabetic white wistar rat model (Rattus norvegicus). This study divided 30 male Wistar rats into 5 groups: negative control (standard feed / K1), positive control of simvastatin with a dose of 0.9 mg / kgBB / Day / K2), and 3 treatment groups were given soursop leaf extract with dose of 75mg / kgBB / day (K3), 150mg / kgBB / day (K4), and 300mg / kgBB / day (K5). Data analysis using One Way Anova and Post Hoc LSD test. The results of this study can be concluded that the administration of Soursop Leaf Extract (Annona muricata) with a dose of 75mg / kgBB, 150mg / kgBB, and 300mg / kgBB can reduce the total cholesterol level of Wistar white rat blood (Rattus norvegicus) hypercholesterolemia-diabetes with a dose of 150mg / kgBB which results in the highest reduction in white wistar rats Wistar hypercholesterolemia-diabetes.